2015
DOI: 10.2486/indhealth.2014-0141
|View full text |Cite
|
Sign up to set email alerts
|

Impact of work-life imbalance on job satisfaction and quality of life among hospital nurses in Japan

Abstract: This study investigated the status of work-life imbalance among hospital nurses in Japan and impact of work-life imbalance on job satisfaction and quality of life. A cross-sectional survey of 1,202 nurses (81% response rate) was conducted in three Japanese acute care hospitals. Participants were divided into four groups for actual work-life balance (Group A: 50/50, including other lower working proportion groups [e.g., 40/50]; Group B: 60/40; Group C: 70/30; and Group D: 80/20, including other higher working p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 20 publications
5
65
1
2
Order By: Relevance
“…This can be supported by the study that was conducted in Japan by Makabe et al. (), which found that job satisfaction and QoL were unsatisfied in nurses who spent more time on work than on their private lives. These results are similar to other studies, which found that WLB has an impact on the QoL of nurses in hospitals (Abraham & D'Silva ; Milosevic et al.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…This can be supported by the study that was conducted in Japan by Makabe et al. (), which found that job satisfaction and QoL were unsatisfied in nurses who spent more time on work than on their private lives. These results are similar to other studies, which found that WLB has an impact on the QoL of nurses in hospitals (Abraham & D'Silva ; Milosevic et al.…”
Section: Introductionmentioning
confidence: 71%
“… A demographic data consisting of 18 items that asked for background information and general job information such as age, gender, working status and shift rotation. A measurement of WLB was adopted from the WLB Charter by the Japanese Cabinet (Makabe et al. ). WLB in this study was determined by the balance between the actual percentage of time spent on work and the percentage of time spent on private life.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychosocial work factors such as skill level, job strain, work‐life balance, psychological job demand, decision latitude, decision authority and job control can also influence QoL. Psychosocial work factors as a whole affected the QoL of male Malaysian automotive factory workers (Edimansyah, Rusli, Naing, Mohamed, & Winn, ); other studies linked QoL with specific aspects, such as job strain (Lerner, Levine, Malspeis, & D'Agostino, ; Tzeng, Chung, & Yang, ), job control (Liang, Hsieh, Lin, & Chen, ), social support (Jönsson, ; Liang et al., ; Tzeng et al., ), work‐life imbalance (Makabe, Takagai, Asanuma, Ohtomo, & Kimura, ), occupational stress and role overload (Wu, Li, Wang, Yang, & Qiu, ) and imbalanced effort/reward (Teles et al., ). However, promotion of work ability can benefit QoL in physical, psychosocial, social relationship and environmental domains (Milosevic et al., ; Sörensen et al., ) and positive correlations between QoL domains and job satisfactions have also been revealed (Cimete, Gencalp, & Keskin, ; Ibrahim et al., ).…”
Section: Introductionmentioning
confidence: 99%